Influence of β-cyclodextrin on the Properties of Norfloxacin Form A - Chierentin, Lucas (2014)
Fil: Chierentin, Lucas. Universidade Estadual Paulista Julio de Mesquita Filho. Faculdade de Ciências Farmacêuticas; Brazil.